Optimalisasi Prestasi Belajar Penjaskes dalam Pembelajaran Online Selama Pandemi: Penelitian Tindakan pada Siswa Sekolah Dasar - Franciska Ilin (Journal of Edukasi Borneo, 2021)
The learning carried out by the teacher is the daily routine of the teaching and learning process at school. The purpose of this study was to determine the improvement of student learning outcomes in physical education, sports and health (Penjaskes) lessons through e-learning in grade 3 Public Elementary Schools (SDN) in Bengkayang Regency. This research was conducted in 2 cycles consisting of the stages of planning, implementation, observation and reflection. The subject of this research was the 3rd grade students of SDN, totaling 28 students. The results of the study showed that through the e-learning could improve student learning outcomes before the action was taken, the average value is 68.57% where there were 12 students who completed and 16 students did not complete, while after being given action in the first cycle, the percentage score was obtained. by 69.28%, where there were 13 students who had completed and 15 students whose learning outcomes had not been completed. Based on the actions taken in the second cycle, the score was 80.71%, where there were 2 students who had not completed and 26 students whose learning outcomes were completed.   ABSTRAK Pembelajaran yamg dilakukan oleh guru merupakan rutinitas harian proses belajar mengajar disekolah. Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar siswa pada pelajaran pendidikan jasmani, olahraga dan kesehatan (Penjaskes) melalui pembelajaran e-learning di kelas 3 Sekolah Dasar Negeri  (SDN)  di Kabupaten Bengkayang. Penelitian ini dilakukan dalam 2 siklus yang terdiri dari tahap perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian adalah ini yaitu siswa kelas 3 SDN yang berjumlah 28 siswa. Hasil penelitian menjelaskan bahwa melalui  model pembelajaran e-learning dapat meningkatkan hasil belajar siswa sebelum dilakukan tindakan diperoleh nilai rata-rata sebesar 68,57 % dimana terdapat 12 siswa yang tuntas dan 16 siswa tidak tuntas, sedangkan setelah diberikan tindakan pada siklus I diperoleh presentase nilai sebesar 69,28%, dimana terdapat 13 siswa yang  tuntas dan  siswa yang hasil belajarnya belum tuntas  15 siswa. Berdasarkan tindakan yang dilakukan pada siklus II diperoleh nilai 80,71 %, dimana terdapat 2 siswa yang belum tuntas dan 26 siswa yang hasil belajarnya tuntas. KATA KUNCI: e-learning, hasil belajar, sekolah dasar